1991
DOI: 10.1111/j.1471-4159.1991.tb02577.x
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine‐Sensitive Calcium Stores in Bovine Adrenal Chromaffin Cells

Abstract: Caffeine was used to study the intracellular Ca2+ pools of bovine chromaffin cells. Its effects on cytosolic Ca2+ concentration ([Ca2+]i) were examined using fura-2. Caffeine caused a transient increase in [Ca2+]i in the presence or absence of extracellular Ca2+. In the former case, the caffeine-induced [Ca2+]i increase was higher and stayed above the basal value for several minutes. In the latter case, the [Ca2+]i rise was lower and fell to the basal level within 1 min. These results suggest that caffeine inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 28 publications
7
33
0
Order By: Relevance
“…The concentration of intracellular Ca 2 + was measured with Fura-2/AM, a calcium fluorescent ester chelator and indicator (Di Virgilio et al, 1988). After glutamate incubation, cells were harvested by gentle scraping, washed and resuspended in a standard medium containing 140 mM NaCl, 5 mM KCl, 1 mM MgCl 2 , 5.6 mM glucose, 1.5 mM CaCl 2 and 20 mM Hepes-Na (final pH 7.4), which was used for loading and for the subsequent fluorescence measurements (Liu et al, 1991). Fura-2/AM (5 mM) was added to the cell suspension, which was subsequently incubated for 30 min.…”
Section: Analysis Of Adenine Nucleotidesmentioning
confidence: 99%
“…The concentration of intracellular Ca 2 + was measured with Fura-2/AM, a calcium fluorescent ester chelator and indicator (Di Virgilio et al, 1988). After glutamate incubation, cells were harvested by gentle scraping, washed and resuspended in a standard medium containing 140 mM NaCl, 5 mM KCl, 1 mM MgCl 2 , 5.6 mM glucose, 1.5 mM CaCl 2 and 20 mM Hepes-Na (final pH 7.4), which was used for loading and for the subsequent fluorescence measurements (Liu et al, 1991). Fura-2/AM (5 mM) was added to the cell suspension, which was subsequently incubated for 30 min.…”
Section: Analysis Of Adenine Nucleotidesmentioning
confidence: 99%
“…The results that the Ca2~re-lease induced by histamine or carbachol, which depends primarily on Ca2~release from 1P 3 stores, was potently inhibited by ryanodine/caffeine, as well as by cinnarizine, indicate that these two ligands activate a large amount ofCa 2tinduced Ca2~release from ryanodine/caffeine stores by causing primary Ca2~release from 1P 3 stores. In fact, it is reported that 1P3 stores have less capacity than caffeine stores in bovine adrenal chromaffin cells (Liu et al, 1991) and that 1P3 caused less Ca 2~release than caffeine in permeabilized chromaffin cells (Robinson and Burgoyne, 1991;Stauderman et al, 1991).…”
Section: Mechanism Of Pacap-induced Ca 2~releasementioning
confidence: 99%
“…The [Ca2~] 1 of a single cell was measured as previously described (Liu et al, 1991). Each chromaffin cell selected for fluorescence measurement was alternately excited at 340 and 380 nm with a dualexcitation fluorometer (CM system, SPEX).…”
Section: Measurement Of [Ca2~] By Fura-2mentioning
confidence: 99%
“…It has also been shown that the nonmitochondrial Ca2* pooi accumulates Ca2b rought into the cells through the voltage-gated Ca2c hannels (Liu et a!., 1991). The ability of this pool to release Ca2~by various Ca2~-re1easingagents has been characterized in detail; however, the physiological role of this pool in bovine chromaffin cells remains unclear.…”
mentioning
confidence: 99%